Late-onset Pompe disease: first case report in Peru - Copaja Corzo, Cesar Augusto (2021)
Introduction: Late-onset Pompe disease is an extremely rare enzyme characterized by incapacitating and progressive neuromuscular damage. There is still no consensus on treatment, but clinical trials have shown that enzymatic replacement with recombinant alpha-glucosidase acid could slow the natural course of the disease and improve prognosis. Clinical case: A 67-year-old man diagnosed with Pompe disease for 4 years, in treatment with physical rehabilitation. He entered the service for right lower limb cellulite that decompensates his background leading to severe respiratory failure. It is admitted to mechanical ventilation, its evolution is torrid due to multiple bacterial infections associated with fan. After 7 months in mechanical ventilation despite multiple weaning attempts, the enzymatic replacement treatment with recombinant acid alpha glucosidase is proposed. Two weeks later, he began improving ventilatory parameters and was discharged after 11 months of hospital stay. Conclusion: Enzymatic replacement treatment with recombinant acid alpha glucosidase showed a positive effect on the evolution of our patient.